2020
DOI: 10.1002/ett.3986
|View full text |Cite
|
Sign up to set email alerts
|

Proxy re‐encryption with equality test for secure data sharing in Internet of Things‐based healthcare systems

Abstract: The integration of the Internet of Things (IoT) and cloud computing brings tremendous convenience and efficiency to process and store growing sensor data in healthcare systems. For the security of sensor data collected by healthcare systems, encrypting data before uploading is necessary. Nevertheless, these encrypted form sensor data make it a research challenge to achieve efficient data search and data sharing on the cloud‐assisted IoT simultaneously. Encrypting data by public key encryption with equality tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
(97 reference statements)
0
16
0
Order By: Relevance
“…They proposed a certificate less Proxy Re‐Encryption (PRE) scheme that realizes secure mobile data sharing and prevents data leakage from cloud proxy server. In a similar work, Li et al 6 suggested a scheme called PRE with equality test for efficient sharing of the searched healthcare data without revealing secret key and plain text. Conventional methods of storing data suffer from data security issues such as leakage, unauthorized access, and centralized storage in spite of the advantages of cloud‐based storage.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed a certificate less Proxy Re‐Encryption (PRE) scheme that realizes secure mobile data sharing and prevents data leakage from cloud proxy server. In a similar work, Li et al 6 suggested a scheme called PRE with equality test for efficient sharing of the searched healthcare data without revealing secret key and plain text. Conventional methods of storing data suffer from data security issues such as leakage, unauthorized access, and centralized storage in spite of the advantages of cloud‐based storage.…”
Section: Introductionmentioning
confidence: 99%
“…Rashad et al [ 23 ] proposed CL-PKC-ET, a certificateless public key cryptography with equality test, to support the ciphertext equality test in IoV. Li et al [ 24 ] designed a cryptographic scheme in IoT-based healthcare systems using proxy re-encryption and ciphertext equality test technology. The scheme realizes the flexible sharing of medical data.…”
Section: Introductionmentioning
confidence: 99%
“…Bhatia et al 6 proposed a lightweight EHR sharing scheme in cloud, which realizes secure data sharing, and cannot leak original EHR to the cloud proxy server. Li et al 7 put forwards a secure data sharing scheme for healthcare systems, which realizes efficiently data search and flexibly data sharing without disclosing the plaintext and the secret key. Although the cloud computing technology realizes the safe storage of EHR, yet the traditional method of cloud storage still brings some problems of data security, such as centralized storage, data availability, privacy leakage, and high computational overhead.…”
Section: Introductionmentioning
confidence: 99%